PEREMPUAN DALAM PARTISIPASI POLITIK DI INDONESIA - Eza Tri Yandy; Muhammad Mustajab (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2021)
Politic is a way to achieve power constitutionally and non constitutionally and in the process of achieving, regulation  are a reference for every indonesian citizen who wants to participate in it. General election, regional head election, which is familiarly known as general election and  local election, is a space for filling certain political positions freely or publicly, which is opened as  wide as possible for the public, social and political inequality that often becomes a problem for women's existence should no longer occur because justice is the right of all citizens in accordance with the mandate of the 1945 constitution article 28 H verse 2. With the laws which is applicable in Indonesia, it is a breath of fresh air for women's struggles, the application of affirmative action with the zipper system method has a positive impact on increasing the existence of women in politics. The existence of women shows positive results as seen from the percentage of women from the election results in 1999 to 2009, in the 2004 and 2009 elections there was an increase in the representation of women in the legislature of the Republic Indonesia because at that time Law Number 12 of 2003 was issued regarding the elections for DPR, DPD and DPRD and reinforced by law number 10 of 2008 article 55 verse 2, only it decreased slightly in the 2014 election and again increased in the 2019 election. The development of the existence of women in politics in Indonesia continues to develop from time to time, this is the impact of the rules or regulations that are made, it is concluded that legal and binding rules are an important indicator for women's groups, the only thing left is the women must maximize available opportunities . From the analysis carried out, the author suggests that the leaders of parties and institutions administering the general election must determine policies and political structures with applicable standardization.